Assessment of bone quality of apical periodontitis treated with MTA plug and regenerative endodontic techniques. (5th October 2022) - Aricioglu, Banu; Gunacar, Dilara Nil; Kosar, Tugba; Sanal Cikman, Ahter; Pertek Hatipoglu, Fatma; Maras, Edanur
Abstract: Fractal analysis (FA) is a quantitative, objective and non‐invasive method that facilitates the characterisation of the tissue architecture. This study aims to compare the periapical healing at 1‐year follow‐up by evaluating newly generated trabecular bone with FA after Mineral trioxide aggregate (MTA) plug and regenerative endodontic treatment (RET). A total of 55 asymptomatic teeth with a single‐canal, open apex and periapical lesion, treated with MTA plug or RET, were evaluated retrospectively. After considering the inclusion/exclusion criteria, FA was conducted on 30 periapical images using the box‐counting method. In both groups, a significant decrease was observed in the periapical lesion size at 1‐year follow‐up ( p < 0.01). However, there was no significant difference between the MTA plug and RET ( p > 0.01). Significantly higher fractal dimension values were detected at 1‐year follow‐up in both MTA plug and RET cases ( p < 0.01). However, the difference was not significant between the groups ( p > 0.01). Both procedures seem to improve periapical healing with a new resistant bone of similar density and complexity.